RELATIONSHIPS BETWEEN KOREAN BRAND AMBASSADOR, PRICE, AND PRODUCT QUALITY TO CUSTOMER PURCHASE DECISION ON LOCAL SKINCARE PRODUCT - Ali Akbar Fuadi; Getruda Filumena Yulius; Christian Haposan Pangaribuan (Milestone: Journal of Strategic Management, 2023)
Nowadays, skincare has evolved into a social trend. People are competing to get the best suitable skincare, while local companies are competing to make skincare that is market-acceptable in terms of image, price, and quality. The usage of Korean brand ambassadors has been a topic in the local skincare industry with some of the recognized brands competing to partner with them. This paper aims to determine if the effort provides a positive relationship with customers’ purchase decision compared to other factors, which are the price and product quality. Using a Likert scale questionnaire distributed to Korean wave fans from high school and college students with a random sampling method, the data is constructed using the regression model. The questionnaire collected 52 participants who have used at least one of the local skincare products that use Korean brand ambassadors. It is found that the brand ambassador and price variable is not significant for the model tested, while product quality positively affects the customers’ purchase decision. The model shows that there is a market segmentation that does not consider the Korean brand ambassador even though they are fans of the Korean wave. Moreover, the market segmentation is also willing to spend more for the product that offers better quality. Therefore, the model suggests that local skincare brands focus more on improving the quality of their product.